STEM Education and Innovative Methods, Integration of Artificial Intelligence in the Learning Process - Tsagareishvili, Nodar (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
This article explores the integration of Artificial Intelligence (AI) into the teaching process of STEM (Science, Technology, Engineering, and Mathematics) subjects. The research examines the role of AI in personalized learning, virtual laboratories, and data analysis, which contribute to students' academic achievements and development of research skills. The study is based on experimental research conducted in schools where AI technologies were implemented in STEM education. The results demonstrate that AI fosters creativity, critical thinking, and significantly improves students' progress in STEM subject.